Evaluation of the United Nations Assistance to the Ivorian Child Refugees in Ghana - Yorke, A. (University of Ghana, 2013)
The term refugee connotes dejection and hopelessness especially for the vulnerable groups such as children, women and the physically challenged. The plights of refugees are often worsened by the fragile economies of host countries particularly in Africa, rise in numbers of refugees globally and the decline in donor support for humanitarian assistance. Nonetheless, the United Nations High Commissioner for Refugees (UNHCR) which is the main body of the UN responsible for humanitarian assistance has over the years not relented in their efforts. They continue to provide food and other relief items, accommodation, health services, counselling and other social services for refugees across the world. But reports from some refugees‟ camps across Africa have revealed that children live under some unpleasant circumstances. Children lack access to education and medicines, while others live in constant fear of rape and abuse by drunken and drug addicted parents and siblings. Some young girls go to the extent of selling their bodies for money because of lack of food. These unfortunate situations are in variance to provisions of the 1989 UN Convention on the Rights of the Child. This study sought to find out whether the UNHCR has drawn lessons from its assistance to children in these camps to better the lives of children in subsequent camps. It evaluated how effectively the UNHCR is meeting the various needs of children in refugee camps and the case in point is the Ivorian refugee children in Ghana who came into the country in 2011 with particular reference to the Ivorian refugee children at the Ampain camp in the western region. The research discovered that UNHCR assistance to refugee children in Ghana is minimal compared to the level and quality of care and protection the children require. Findings also brought to the fore pertinent issues such as security at the camps, access to tertiary and vocational education for adolescent children, nutritional supplement for malnourished children and improvement in food and other relief supplies for children which need to be addressed by UNHCR and its partner agencies.
Thesis (MA)-University of Ghana, 2013